Age, β-endorphin, and sex dependent effects of maternal separation on locomotor activity, anxiety-like behavior, and alcohol reward - Scopano, Madison R.; Jones, Holly E.; Stea, Sam G.; Freeman, Maya Z.; Grisel, Judith E. (Frontiers in Behavioral Neuroscience, 2023)
Childhood adversity is pervasive and linked to numerous disadvantages in adulthood, including physical health problems, mental illness, and substance use disorders. Initial sensitivity to the rewarding effects of alcohol predicts the risk of developing an alcohol use disorder, and may be linked to developmental stress. The opioid peptide β-endorphin (β-E) regulates the stress response and is also implicated in the risk for excessive alcohol consumption. We explored the influence of β-E in an animal model of early life adversity using controlled maternal separation by evaluating changes in locomotor activity, anxiety-like behavior, and the initial rewarding effects of alcohol in a single exposure conditioned place preference paradigm in control C57BL/6J and β-E deficient β-E +/+.129S2-Pomc tm1Low /J; β-E -/- mice. Maternal separation (MS) occurred for three hours each day from postnatal days (PND) 5-18 in approximately half the subjects. Maternal interactions increased following the separation protocol equally in both genotypes. MS and control subjects were tested as adolescents (PND 26-32) or adults (PND 58-72); the effects of MS were generally more pronounced in older subjects. Adults were more active than adolescents in the open field, and MS decreased activity in adolescent mice but increased it in adults. The increase in activity in adults as a result of early life stress depended on both β-E and sex. β-E also influenced the effect of maternal separation on anxiety-like behavior in the Elevated Plus Maze. MS promoted rewarding effects of alcohol in male β-E deficient mice of either age, but had no effect in other groups. Taken together, these results suggest that the effects of MS develop over time and are β-E and sex dependent.